The Role of Microbiome in Insomnia, Circadian Disturbance and Depression - Li, Yuanyuan; Hao, Yanli; Fan, Fang; Zhang, Bin (Frontiers in Psychiatry, 2018)
Good sleep and mood are important for health and for keeping active. Numerous studies have suggested that the incidence of insomnia and depressive disorder are linked to biological rhythms, immune function and nutrient metabolism, but the exact mechanism is not yet clear. There is considerable evidence showing that the gut microbiome not only affects the digestive, metabolic, and immune functions of the host but also regulates host sleep and mental states through the microbiome-gut-brain axis. Preliminary evidence indicates that microorganisms and circadian genes can interact with each other. The characteristics of the gastrointestinal microbiome and metabolism are related to the host’s sleep and circadian rhythm. Moreover, emotion and physiological stress can also affect the composition of the gut microorganisms. The gut microbiome and inflammation may be linked to sleep loss, circadian misalignment, affective disorders and metabolic disease. In this review article, we discuss various functions of the gut microbiome and how its activities interact with the circadian rhythms and emotions of the host. Exploring the effects of the gut microbiome on insomnia and depression will help further our understanding of the pathogenesis of mental disorders. It is therefore important to regulate and maintain a normal gastrointestinal micro-ecological environment in patients when treating mental disorders.